"Thinking about drinking": Exploring children's perceptions of alcohol using the Draw and Write tool. Issue 6 (3rd October 2016) - Farmer, Siobhan; Porcellato, Lorna
Abstract : Purpose: The purpose of this paper is to explore perceptions of alcohol held by schoolchildren using the "Draw and Write" tool, to inform the planning of alcohol education in the classroom setting. Design/methodology/approach: A specifically designed "Draw and Write" booklet was used with 169 children aged nine to ten years (Year 5) across seven primary schools in a small Local Authority in North West England. Written responses were thematically coded. Findings: Results demonstrated that the children had a good basic understanding of alcohol, including who drinks, where it can be purchased and the range of products available. Participants were aware that alcohol could be harmful and held mainly negative views. Findings suggest that alcohol education at this age is both appropriate and necessary to help children explore, understand and clarify their perceptions and misconceptions in a safe classroom environment. Practical implications: The range and depth of responses from the children demonstrated that Draw and Write can be used successfully to explore children's perceptions of alcohol. The tool can be used as a baseline assessment to inform classroom-based alcohol education for primary school teachers and those supporting delivery at local level, in line with national policy recommendations. Originality/value: This paper adds to the existing literature on the use of "Draw and Write" in personal, social and health education, demonstrating that it can be used specifically to investigate children's knowledge and attitudes about alcohol.